Mini-open transosseous repair with bursal augmentation improves outcomes in massive rotator cuff tears - Yasser El Safoury; Ahmed O. Sabry (Scientific Reports)
Abstract Treatment of Massive rotator cuff tears (MRCT) is difficult, with high rates of retears. Using biological augmentation in the form of the highly vascular subacromial bursa, was used to improve tendon healing. This work aimed to evaluate the results of arthroscopic guided mini-open transosseous repair with bursal augmentation in the treatment of MRCTs in a five-step approach. Forty-eight patients, with a mean age of 63.15 years, were treated with this technique. The patients were evaluated with the constant, UCLA and VAS scores. Plain X-rays were performed to evaluate the CSA and MRI was done to confirm the diagnosis of MRCT and determine the degree of fatty degeneration. Ultrasound was done at 1 year post-operative to determine any retears. The mean follow-up period was 29 months ± 4.95. The Constant and UCLA mean scores improved from (52.52) to (89) and (13.2) to (30.5) respectively (p < 0.0001). The post-operative active flexion and abduction improved from a mean of (112° to 170°) and (136.2° to 167°) respectively, while ER improved from (62.8° to 70°) with their p values (p < 0.0001). Pain improved from a mean VAS of (5.85) to (0.5) (p < 0.0001). No deterioration of function was noted throughout the follow-up period, and no retears occurred on post-operative ultrasound evaluation. Mini-open transosseous repair with bursal augmentation in the treatment of MRCT is an effective and low-cost method that achieves satisfactory results with no retears.